(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
English use on Mukalla street signs is examined in this study. The paper is an attempt to study how the morphological structure of Arabic has been affected by English sings using at Mukalla streets. Yemen ; on shops, mini-markets, supermarkets, net-cafes, Moles and companies, among others. Moreover, the Yemeni customers’ attitudes to the use of English loan words along with Arabic is also evaluated. 180 sings chosen randomly have been examined linguistically to find out if there is any particular influence of English over Arabic morphological structure of the street signs. In addition, a questionnaire was given to the participants to show their attitudes toward using English sings. The population of the study consisted of all the students at Hadramout University, English Departments, Faculty of Arts and Women’s College. They are from different places in Yemen. The findings indicate that the loan words are altering to suit the morphological structure and so become a part of Arabic structure where they substitute the identical ones. The participants attitudes towards these signs have shown that they are aware of and loyal to their own language. However, they prefer using English for commercial reasons.